2022
DOI: 10.1021/acs.macromol.2c00543
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cation–Ligand Interactions on the Permselectivity of Ligand-Functionalized Polymer Membranes in Single and Mixed Salt Systems

Abstract: We conduct molecular dynamics simulations to study the effects of cation–ligand interactions on salt permeation in ligand-functionalized polymer membranes. Our results indicate that salt partitioning into the membrane increases while the salt diffusivity decreases with enhancement in the cation–ligand interaction strength. Moreover, the increase in partitioning dominates the decline in salt diffusivity, leading to a net enhancement in salt permeation at higher cation–ligand interaction strengths. Equimolar bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 45 publications
3
21
3
Order By: Relevance
“…The net effect on S i/j , hence, depends on the modifications to , , , and , and the eventual outcome on separation selectivity can swing either way. While the previous studies reported selective transport of the complexed ion (Chaudhury et al, 2014;Sheng et al, 2014;Tas et al, 2016;DuChanois et al, 2022;Sachar et al, 2022), a recent atomistic molecular dynamics simulation found that coordination chemistry will actually favor the transport of noncomplexing species (Zofchak et al, 2022). The reversal in trend is caused by exceedingly strong ligand-ion interactions drastically retarding mobility of the coordinated ion, overwhelming the benefits of higher partitioning.…”
Section: Specific Ion Selectivitymentioning
confidence: 94%
“…The net effect on S i/j , hence, depends on the modifications to , , , and , and the eventual outcome on separation selectivity can swing either way. While the previous studies reported selective transport of the complexed ion (Chaudhury et al, 2014;Sheng et al, 2014;Tas et al, 2016;DuChanois et al, 2022;Sachar et al, 2022), a recent atomistic molecular dynamics simulation found that coordination chemistry will actually favor the transport of noncomplexing species (Zofchak et al, 2022). The reversal in trend is caused by exceedingly strong ligand-ion interactions drastically retarding mobility of the coordinated ion, overwhelming the benefits of higher partitioning.…”
Section: Specific Ion Selectivitymentioning
confidence: 94%
“…Such trends arise as a result of a reduction in the self-diffusivity of the LS cations as discussed in our previous work. 23 Similarly, the true salt diffusivity ratio also decreases with an increase in ϵ LS Cation-Ligand . However, in comparing the two results (ideal and true salt diffusivity ratios), ionic correlations are seen to increase the salt diffusivity ratio at high LS cation−ligand interaction strengths (ϵ LS Cation-Ligand / k B T > 3.0) but have negligible impact on the salt diffusivity ratio at low LS cation−ligand interaction strengths (up to ϵ LS Cation-Ligand /k B T = 3.0).…”
Section: Impact Of Ionic Correlations In Mixed Saltmentioning
confidence: 94%
“…The ideal salt diffusivity ratio [i.e., D LS Salt ideal /D LA Salt ideal ] decreases with increasing ϵ LS Cation-Ligand primarily because of the reduction in the LS cation self-diffusivity as discussed in our previous manuscript. 23 From Figure 2b, the true salt diffusivity ratio [i.e., D LS Salt GK / D LA Salt GK ] is seen to be lower than the ideal salt diffusivity ratio (albeit only marginally) at low values of ϵ LS Cation-Ligand (ϵ LS Cation−Ligand /k B T = 1, 2, 3), whereas the converse is true at relatively high values of ϵ LS Cation-Ligand (ϵ LS Cation−Ligand /k B T = 4, 5, 6). In other words, ionic correlations are seen to reduce (marginally enhance) the selective transport of LA salt relative to LS salt at high (low) LS cation−ligand interaction strengths.…”
Section: Impact Of Ionic Correlations In Single Saltmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wieland et al observed that the measured conductivities in such systems are only a fraction of the conductivity expected based on the ideal (Nernst–Einstein) ion diffusivities . Simulation results demonstrated such observations to be a consequence of dynamical correlations, that is, the influence of dynamics of one or more of the ions on the motion of a different ion. , In the case of polyILs, such correlations were shown to arise from both between the mobile ion and the immobilized ions on the polymer backbone. Studies in the context of solvated polyelectrolytes have also demonstrated similar results and underlying mechanisms. , …”
mentioning
confidence: 99%